Satisfaction and Opinions of Tehran University of Medical Sciences Academic Members on Its Development Programs , 2006 - j Gholami; SH Nejat; R Majdzadeh; A Rashidian (Tehran University of Medical Sciences, 2008)
Background and Aim: Surveying faculty members can prove beneficial in the assessment of the university's performance in various domains, and the design and planning of suitable interventions. The current study assesses faculty members' opinions on the university's development programs.Materials and Methods: One hundred and forty nine individuals completed the questionnaire in this cross-sectional study that was done through systematic sampling. The questionnaire covered demographic questions, professional specifications, faculty promotion criteria, sabbatical leaves, faculty participation in short-term educational programs, being in contact with graduates, recruiting foreign students, distant learning, processes involving research proposal approval, rewards and encouragement policies, faculty participation in health care management and distribution of budget among schools and hospitals.Results: 71.8% of participants were male. The mean numbers of years of service in the university was 14.2 with a standard deviation of 7.5. Most participants were satisfied with the current status of promotion, processes involving research proposal approval and their participation in short-term educational programs. However most were not happy with the current status of sabbatical leaves.Conclusion: Surveying through the methodical approach is a valuable tool in guiding senior university directors and its repetition and continuity can strengthen faculty participation and assess changing procedures.